The future of law and economics : essays in reform and recollection - Calabresi, Guido, 1932- (New Haven : Yale University Press, 2016)
In a concise, compelling argument, one of the founders and most influential advocates of the law and economics movement divides the subject into two separate areas, which he identifies with Jeremy Bentham and John Stuart Mill. The first, Benthamite, strain, 'economic analysis of law,'; examines the legal system in the light of economic theory and shows how economics might render law more effective.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 18, 2016).
Keywords: Law and economics; Law; Economic theory & philosophy; Jurisprudence & general issues; Methods, theory & philosophy of law